Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1289/ehp.0800465
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Personal Exposure to Airborne Benzene and Intrauterine Growth

Abstract: BackgroundStudies relying on outdoor pollutants measures have reported associations between air pollutants and birth weight.ObjectiveOur aim was to assess the relation between maternal personal exposure to airborne benzene during pregnancy and fetal growth.MethodsWe recruited pregnant women in two French maternity hospitals in 2005–2006 as part of the EDEN mother–child cohort. A subsample of 271 nonsmoking women carried a diffusive air sampler for a week during the 27th gestational week, allowing assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
103
0
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 44 publications
(78 reference statements)
3
103
0
11
Order By: Relevance
“…Elevated rate of low birth weights have been reported by Slama et al (2009) in a cohort study of 271 non-smoking pregnant women exposed to benzene via inhalation at median concentration of 0.0018 mg/m 3 (Slama et al, 2009). Chen et al (2000) also reported low birth weights of fetuses born to women exposed to benzene at 0.0543 to 0.61mg/m 3 in a petrochemical industry (Chen et al, 2000).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Elevated rate of low birth weights have been reported by Slama et al (2009) in a cohort study of 271 non-smoking pregnant women exposed to benzene via inhalation at median concentration of 0.0018 mg/m 3 (Slama et al, 2009). Chen et al (2000) also reported low birth weights of fetuses born to women exposed to benzene at 0.0543 to 0.61mg/m 3 in a petrochemical industry (Chen et al, 2000).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Desse modo, os níveis de O 3 estimados nesses estudos podem não refletir os verdadeiros níveis de O 3 , aos quais as gestantes foram expostas. Além disso, assim como o O 3 , neste estudo, outros poluentes, como o benzeno e MP 10 , influenciaram negativamente o crescimento da CC durante a gestação (29,31) .…”
Section: Biometria Fetalunclassified
“…Slama et al (29) , seguindo uma coorte de 271 gestantes não tabagistas, observaram que a CC sofreu influência negativa do benzeno, que foi utilizado em seu estudo como proxy da exposição ao tráfego de veículos, porém a exposição à poluição foi avaliada, somente durante 7 dias, em apenas um momento da gestação (27 a semana). Dessa forma, não foi possível verificar a variabilidade da exposição à poluição durante a gestação e qual seria a janela crítica de exposição que mais afetaria o desenvolvimento fetal.…”
Section: Biometria Fetalunclassified
See 2 more Smart Citations